Institutions and market distortions: international evidence for tobacco - Beghin, John C.; Foster, William E.; Kherallah, Mylene (Wiley, 1996)
The link between institutional factors and agricultural protection levels is investigated using cross‐section time series data on three tobacco types. The analysis includes the presence of monopsonistic marketing agencies, political institutions, and the feasibility of tax revenue collection and diversification. Protection increases with economic development and with well functioning direct taxation systems, but tends to be lower in the most advanced pluralistic democracies. The presence of strong anti‐smoking interest groups seems to galvanise the lobbying effort of tobacco farmers — higher protection is associated with that presence.